Synergistic effect of whey proteins and their derived microgels in the stabilization of O/W emulsions - Silva, Jéssica Thaís do Prado [UNESP]; Janssen, Annabel; Nicoletti, Vânia Regina [UNESP]; Schroën, Karin; de Ruiter, Jolet (My University, 2023)
Tannic acid-crosslinked whey protein isolate (TA-WPI) microgels can physically stabilize food emulsions by adsorption to the oil-water interface. Production of these particles is often accompanied by residual un-reacted WPI, which may play a role in the stabilization of emulsions. Here, TA-WPI microgels were produced and the presence and composition of surface-active molecules was characterized using ultrafiltration. Full purification was not feasible; the final dispersion used for emulsification had microgels and free protein in a ∼20:1 mass ratio, both of them enriched in β-lactoglobulin compared to the starting material. The physical characteristics of emulsions stabilized by blends of microgels and native WPI depended on the homogenization method used. When using low-shear methods (rotor-stator), microgels suppressed coalescence by bridging flocculation, which was disrupted by WPI over 14 days of storage. On the other hand, emulsions produced under high shear (microfluidizer) were very viscous, and highly flocculated, and they remained in the flocculated form after 14 days of incubation, which may be due to strong anchoring of adsorbed microgels caused by the high energy provided to the system during the homogenization procedure.
Keywords: Bridging flocculation; Mixed systems; Particle-stabilized emulsions; Surface-active molecules; Tannic acid; WPI microgels